2018
DOI: 10.2169/internalmedicine.9889-17
|View full text |Cite
|
Sign up to set email alerts
|

Multiple White and Flat Elevated Lesions Observed in the Stomach: A Prospective Study of Clinical Characteristics and Risk Factors

Abstract: Objective Multiple white and flat elevated lesions (MWFLs) observed in the stomach have only been presented in abstracts at academic conferences over the last decade; therefore, relatively little is known about these lesions. Our aim was to prospectively clarify the clinical characteristics of MWFLs, to identify their risk factors and to retrospectively evaluate the clinical progression of these lesions. Methods A prospective analysis of clinical characteristics and risk factors was conducted in participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…(6) An association between the presence of multiple white elevated lesions and PPI use has been reported. (5,6,15) The high frequency of female gender and advanced age in patients with the morphological changes in the present study is consistent with previous Japanese studies. (5,9,15) Among healthy individuals, postprandial gastrin levels in women are two-to three-fold higher than in men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(6) An association between the presence of multiple white elevated lesions and PPI use has been reported. (5,6,15) The high frequency of female gender and advanced age in patients with the morphological changes in the present study is consistent with previous Japanese studies. (5,9,15) Among healthy individuals, postprandial gastrin levels in women are two-to three-fold higher than in men.…”
Section: Discussionsupporting
confidence: 93%
“…(5,6,15) The high frequency of female gender and advanced age in patients with the morphological changes in the present study is consistent with previous Japanese studies. (5,9,15) Among healthy individuals, postprandial gastrin levels in women are two-to three-fold higher than in men. (16) During GERD therapy with PPIs, women also have higher gastrin levels compared to men.…”
Section: Discussionsupporting
confidence: 93%
“… 10 , 33 In observational studies, multiple white and flat elevated lesions were found to be significantly associated with PPI use (OR, 3.58; 95% CI, 1.94 to 6.61), H. pylori eradication therapy (OR, 2.11; 95% CI, 1.08 to 4.11), female sex (OR, 1.92; 95% CI, 1.19 to 3.12), aging (OR, 1.05; 95% CI, 1.02 to 1.08), and moderate to severe atrophic gastritis (OR, 2.63; 95% CI, 1.52 to 5.63). 12 , 33 - 35 These lesions are also related with administration of histamine receptor antagonists and H. pylori eradication, and are therefore not uniquely associated with chronic PPI use. Furthermore, these lesions can be misdiagnosed as intestinal metaplasia.…”
Section: Endoscopic Features Of Ppi-related Gastric Mucosal Changesmentioning
confidence: 99%
“…Other findings are less well understood, such as the presence of ‘WFELs’ which are observed in the fundus of an H pylori- naïve and H pylori -eradicated stomach, although are of uncertain clinical significance. 49 The included studies make reference to WFELs but did not include data to analyse their significance. Similarly, it was not possible to provide new diagnostic accuracy calculations for the findings of gastric hyperplastic polyps or xanthomas because of paucity of data.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric erosions 9.0 (4.9-15.9) 93.4 (83.6-97. significance. 49 The included studies make reference to WFELs but did not include data to analyse their significance. Similarly, it was not possible to provide new diagnostic accuracy calculations for the findings of gastric hyperplastic polyps or xanthomas because of paucity of data.…”
Section: Sensitivity (95% Ci) Specificity (95% Ci) Dor (95% Ci) Aurocmentioning
confidence: 99%